ANALISIS KEPEMIMPINAN PENDIDIKAN DI INDONESIA DAN CHINA DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN - Sri Adhi Endaryati; Sri Marmoah (Universitas Muhammadiyah Surakarta, 2022)
Principals of Elementary Schools have an effect on improving the quality of education. This research is a descriptive qualitative research. The aim of this research is to describe the leadership of elementary schools in Indonesia and China. Data and data sources are taken from interviews and questionnaires. Sources of literature review data in the form of journals, books, and articles are more effective. Qualitative research methods to enrich information data in depth about the problem to be solved. Data collection techniques with questionnaires, interviews, and literature review. The research data analysis technique is an interactive model of Miles and Huberman which begins with collecting raw data, displaying data, reducing data, verifying data, and concluding data. The results showed that the principal’s leadership influenced the improvement of the education quality of school institutions. Primary school leadership in Indonesia and China share a common commitment to realizing the vision and mission for the advancement of school quality, communicating with teachers about the vision and mission to be achieved, empowering the work climate for teachers professional performance. The difference between principal’s leadership in Indonesia and China lies in the dedication of working time in China is longer than the working time of principals in Indonesia. Indonesia with democratic leadership while China with instructional leadership It is hoped that school principals can improve performance and leadership quality for the advancement of education in Indonesia so as to produce quality and competitive output in 21st century life.